Impairment of Muscle Function Causes Pupal Lethality in Flies Expressing the Mitochondrial Alternative Oxidase - Carlos A. Couto-Lima; Sina Saari; Geovana S. Garcia; Gabriel H. Rocha; Johanna ten Hoeve; Eric Dufour; Marcos T. Oliveira (Biomolecules)
The mitochondrial alternative oxidase (AOX) from the tunicate Ciona intestinalis has been explored as a potential therapeutic enzyme for human mitochondrial diseases, yet its systemic effects remain poorly understood. Here, we investigate the metabolic and physiological consequences of AOX expression during the development of Drosophila cultured under dietary stress. We show that the combination of strong, ubiquitous AOX expression and a low-nutrient condition leads to pupal lethality and severe defects in larval musculature, characterized by actin aggregation and muscle shortening. These structural abnormalities correlate with a decrease in larval biomass and motility. Interestingly, the muscle defects and the motility impairments vary in severity among individuals, predicting survival rates at the pupal stage. AOX expression in specific tissues (muscle, nervous system or fat body) does not individually recapitulate the lethal phenotype observed with ubiquitous expressions of the enzyme, indicating a complex metabolic imbalance. Metabolomic analysis revealed that the low-nutrient diet and AOX expression have opposite effects on most metabolites analyzed, especially in the levels of amino acids. Notably, supplementation of the low-nutrient diet with the essential amino acids methionine and/or tryptophan partially rescues pupal viability, body size, muscle morphology, and locomotion, whereas supplementation with proline and/or glutamate does not, highlighting a specific perturbation in amino acid metabolism rather than general bioenergetic depletion. These findings demonstrate that AOX expression disrupts metabolic homeostasis, with developmental and physiological consequences that must be considered when evaluating AOX for therapeutic applications.